2017
DOI: 10.1186/s12978-017-0370-x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of disrespect and abuse during facility-based maternity care in Malawi: evidence from direct observations of labor and delivery

Abstract: BackgroundThere is increasing evidence throughout the world that the negative treatment of pregnant women during labor and delivery can be a barrier to seeking skilled maternity care. At this time, there has been little quantitative evidence published on disrespect and abuse (D&A) in Malawi. The objective of this research is to describe the prevalence of disrespect and abuse during labor and delivery through the secondary analysis of direct clinical observations and to describe the association between the obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
47
7
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 13 publications
16
47
7
2
Order By: Relevance
“…Nevertheless, studies have reported issues with the misuse of birth companions who mostly provide instrumental support to care providers [20] and underutilization [21] in resource-limited settings. Birth companions rarely accompany a pregnant woman to the labor ward during childbirth but are sometimes allowed into the labor ward to intimidate and force the pregnant woman to cooperate with care providers' demands [22].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, studies have reported issues with the misuse of birth companions who mostly provide instrumental support to care providers [20] and underutilization [21] in resource-limited settings. Birth companions rarely accompany a pregnant woman to the labor ward during childbirth but are sometimes allowed into the labor ward to intimidate and force the pregnant woman to cooperate with care providers' demands [22].…”
Section: Introductionmentioning
confidence: 99%
“…In a review article in Iran, Azami et al (2014) found that in nearly 40% of the cases, mothers selected cesarean section because of their fear of NVD [12]. There is also evidence that mothers may not seek maternity care, if they face D&A [13]. The WHO emphasized the important role of RMC in statements entitled "RMC improves lactation" [14] and "recommendations for improving the childbirth experience" [15].…”
Section: Introductionmentioning
confidence: 99%
“…D&A can apparently constitute a barrier to facility delivery with its attendant complications, including maternal mortality [7]. Many factors have been identified to contribute to D&A in health facilities such as poor communication between women and healthcare providers; inadequate healthcare policies; prejudices from healthcare providers; and demoralization of healthcare providers in poorly performing health facilities [6,9,10].Although there are variations in prevalence, reports of high prevalence rates of D&A among women during facility birth have been documented in several countries [8,11,12]. For instance, approximately 13-28%women who accessed obstetrics and gynaecology services in Northern Europe experienced some form of abuse in healthcare centres [8].…”
Section: Introductionmentioning
confidence: 99%